Microbial Enhanced Oil Recovery (MEOR): Alternatif Peningkatan Produksi Migas di Indonesia - Desy Hikmatul Siami; Novi Hery Yono (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2020)
The need for petroleum is increasing along with the development of the industry, while the production results from the process of recovering oil from the reservoir by using primary recovery and secondary recovery are still very low so that it takes an advanced stage, namely tertiary recovery or, known as EOR. EOR is a method that produces oil production above 50%. EOR is an effort to increase oil production, so it is included in the IOR (Improved Oil Recovery) section. EOR consists of various applications, ranging from water injection, chemical injection, gases injection to microbiology injection. The stages in the injection of water and gas still leave oil trapped in the rocks in the reservoir. MEOR is one method that can be used to bring oil trapped in reservoir rocks to the surface. The effectiveness of the MEOR method is measured based on several parameters that is formation temperature, oil viscosity, permeability, saltwater salinity, water cut, API gravity crude oil, pH, pressure, residual oil saturation, porosity depth and bacterial content in the reservoir.